Plane wave scattering on chain of silver nanowires - Stogniy, N. P.; Sakhnenko, N. K. (ФНТ, 2011)
The problem of electromagnetic interaction of two or more closely spaced nanoparticles is of great importance. Such configurations give rise to tunable spectral shifts of the plasmon bands and to exceptionally strong field enhancements. Indeed, the general interest in this field has strongly increased in recent years as improved nanofabrication methods now allow advanced control of nanoparticle shape and arrangement patterns of particle ensembles. In this paper we consider H-polarized plane wave scattering on a linear chain of N identical infinite-long silver cylindrical nanowires. The main goal is to investigate the plasmon resonances of the structure. The Mie series expansion is used to derive the solution. For the refractive index value we use the experimental data obtained by Jonson and Christie for bulk silver.
Keywords: plane wave; nanowires